Is the family at risk if collapse? The condition of the Polish family in comparison to the other European countries - Gębuś, Dorota (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
During last decades peoples’ attitude to marriage, family and raising children have changed. In Poland we have to deal with a decreasing number of marriages, a rising number of divorces, and new forms of family life. There are more and more people living alone or in cohabitation. More and more of us are raising children alone or living in a childless marriage. The labour market has forced people to change their values connected with individualism and individual autonomy that has caused a gradual vanishing of the traditional family mode. Employers have big requirements, so only people who are well-educated and are able to sacrifice for career can cope with it. It is more and more difficult to reconcile work with family life because both of them impose obligations. The other problem is a bad economic situation. It is connected with unemployment, low salary and poverty. Financial assistance in Poland is much lower than in other European countries. In comparison to citizens of the EU, people in Poland spend more time on working but earn less. Consequently we have less time for family and we have worse economic conditions. This situation is not conductive to make a decision about starting a family. Within the last 20 years a very big decline in fertility rate has been seen. At the moment we are in the group of European countries in which children are born the least. For most young people one of the solutions is emigration and settlement in countries where they have an opportunity to get a permanent job, a good salary and high social benefits. This article shows an analysis of selected demographic and economic indicators that illustrates the condition in which the Poland is nowadays.
Keywords: Polish family; work; demographic situation